PERAMALAN HARGA SAHAM NVIDIA DENGAN METODE DOUBLE MOVING AVERAGE - Alief Prima Gani; Tundo Tundo; Ridho Akbar; Kevin Arya Josaphat Sitompul (Jurnal Ilmiah Informatika Komputer, 2024)
The movement of NVIDIA's stock price greatly affects investment decisions, so accurate forecasting is very important to influence investment decisions. This research will apply the data mining process for forecasting NVIDIA stock prices using the Double Moving Average method with the application of order 2 and order 3 models. The purpose of this study is to determine the forecasting of the NVIDIA stock price index based on historical data.  The results show that stock price forecasting using the Double Moving Average method order 2 model is more accurate and in accordance with actual or actual results. On the other hand, forecasting the Double Moving Average method with the order 3 model produces unsatisfactory forecasts that can be used, making it less suitable for dynamic markets. Therefore, the results of forecasting NVIDIA stock prices using the Double Moving Average method order 2 obtained an accuracy of 98% compared to order 3 of 67%. Based on the comparison results of using orders 2 and 3, it can be an important factor for investors to help make investment decisions in terms of forecasting the next production of NVIDIA shares.